Dual-task related frontal cerebral blood flow changes in older adults with mild cognitive impairment: A functional diffuse correlation spectroscopy study - Udina, Cristina; Avtzi, Stella; Mota-Foix, Miriam; Rosso, Andrea L.; Ars, Joan; Kobayashi Frisk, Lisa; Gregori-Pla, Clara; Durduran, Turgut; Inzitari, Marco (Frontiers in Aging Neuroscience, 2022)
In a worldwide aging population with high prevalence of motor and cognitive impairment, it is paramount to improve knowledge about underlying mechanisms of motor and cognitive function and their interplay in aging processes. We measured prefrontal cerebral blood flow (CBF) using functional diffuse correlation spectroscopy during motor and dual-tasks. We aimed to compare CBF changes among 49 older adults with and without mild cognitive impairment (MCI) during a dual-task paradigm (normal walk, 2-forward count walk, 3-backward count walk, obstacle negotiation and heel tapping). Participants with MCI walked slower during normal walk and obstacle negotiation, compared to participants with normal cognition (NC), while gait speed during counting conditions were not different between groups, so that the dual-task cost was higher for NC participants. We built a linear mixed effects model with CBF measures from right and left prefrontal cortex. MCI (n=34) showed a higher increase in CBF from normal walk to 2-forward count walk (estimate = 0.34, 95%CI [0.02, 0.66], p=0.03) compared to NC participants, related to a right-sided activation. Both groups showed a higher CBF during 3-backward count walk compared to normal walk, while only among MCI, CFB was higher during 2-forward count walk. Our findings suggest a differential prefrontal hemodynamic pattern in older adults with MCI compared to NC counterparts during dual-task performance, possibly as a response to increasing attentional demand.